Introgression among subgroups is an important driving force for genetic improvement and evolution of the Asian cultivated rice Oryza sativa L. - Zhou, Jiawu; Li, Jing; Zhang, Yu; Yang, Ying; Lv, Yonggang; Pu, Qiuhong; Deng, Xianneng; Tao, Dayun (Frontiers in Plant Science, 2025)
Anagenesis accumulates favorable mutations that enable crops to adapt to continually improving artificial production environments, while cladogenesis results in the deposition of beneficial variations across diverse ecotypes. Integrating advantageous genetic variations from diverse evolutionary sources establishes the foundation for the continued genetic improvement of crops. For a long time, rice breeding practices have been guided by the established belief that the Asian cultivated rice consists of two subspecies: Oryza sativa subsp. indica and subsp. japonica. Integrating elite genetic variants from both subspecies has been a major strategy for genetic improvement. This approach has proven successful through the achievements of temperate japonica breeding programs in China, Japan, and Korea over the past decades. The genetic differentiation within the Asian cultivated rice has been successfully harnessed for heterosis breeding, thereby enhancing rice yield productivity. Genomic investigations have revealed more genetic divergences in the Asian cultivated rice, prompting the proposal of six subgroups within it. This indicates that there is greater potential for uncovering additional genetic divergences and diversity in future breeding practices. Genetic introgression and gene flow among subgroups have led to improvements in agronomic traits within the indica, temperate japonica, and tropical japonica subgroups during the modern rice breeding process. The introgression process has widened the genetic diversity within subgroups and reduced the genetic distance between them, resulting in the creation of new genetic blocks and subpopulations. Artificial introgression has accelerated the evolution process in rice breeding history. Advancements in the study of genetic divergence and diversity in rice offer valuable insights to guide breeding practices. The mini subgroups aus, basmatic, and rayada possess untapped genetic potential but have been poorly studied worldwide; more samples should be further investigated. This information will be invaluable for harnessing these advantageous variations through introgression breeding. Further studying the nature of reproductive barriers among subgroups will enhance our understanding of genetic differentiation, allow us to overcome these barriers and facilitate effective genetic exchange, and even enable us to harness heterosis among subgroups.